Creation on the basis of the first theory of strength model equal stressed cylinder exposed to power and temperature loads - Andreev Vladimir; Leontyev Andrey (MATEC Web of Conferences, 2017)
The paper discusses the axially symmetric plane problem theory of elasticity for inhomogeneous thick-walled cylinder under the action of external pressure and stationary temperature field. The essence of the inverse problem is to determine such dependence of the modulus of elasticity on the radius at which the stress state of the cylinder will be given. It should be noted that an equal stressed cylinder does not coincide with an equal strength cylinder [1] since when the modulus of elasticity of a material changes by modifying its composition, as a rule, its strength properties also change.